The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s42330-020-00132-4
|View full text |Cite
|
Sign up to set email alerts
|

When I Believe, I Can: Success STEMs from My Perceptions

Abstract: The increasing concern in North America regarding the workforce’s ability to maintain a competitive position in the global economy has led to an increased interest in effective science, technology, engineering, and mathematics (STEM) education. The purpose of this study was to investigate the effect of engaging in STEM project-based learning (PBL) activities on students’ mathematical problem-solving beliefs (PSB) and their perceptions towards SEM subjects and STEM careers. The data were collected using mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 65 publications
(67 reference statements)
3
17
0
1
Order By: Relevance
“…This result may prove that students realized the relationship between nature and science, and that positive changes in the discovery of science in nature occurred. Similarly, Kwon, Capraro and Capraro (2021) stated in their study that STEM-based students had positive changes in their opinions about science and mathematics, and their career perceptions, and developed awareness for the future.…”
Section: Discussion and Conclusion Changes In The Ways To Express Con...mentioning
confidence: 92%
See 1 more Smart Citation
“…This result may prove that students realized the relationship between nature and science, and that positive changes in the discovery of science in nature occurred. Similarly, Kwon, Capraro and Capraro (2021) stated in their study that STEM-based students had positive changes in their opinions about science and mathematics, and their career perceptions, and developed awareness for the future.…”
Section: Discussion and Conclusion Changes In The Ways To Express Con...mentioning
confidence: 92%
“…In recent years, it has been aimed at students experiencing science, mathematics, engineering, technology, and art components in an interdisciplinary way in science and nature camps through STEM and STEAM. Kwon, Capraro, and Capraro (2021) stated in their study that STEM-based students had positive changes in their opinions about science and mathematics. In the research conducted, it is highlighted that components, especially art, should not be product-oriented but process-oriented in these interdisciplinary studies (Perignat & Katz-Buonincontro, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…In general, results from recent research found a positive shift in learners' perceptions and attitudes towards STEM disciplines and careers at the completion of their engagement in a STEM-focused program in an out-of-school context [35,[39][40][41][42][43]. For example, Baran et al [35] examined the impact of an afterschool program designed to engage forty 10-12-year-old learners in hands-on STEM problem-based activities.…”
Section: Learners' Perspective Of Stemmentioning
confidence: 99%
“…Selain keterlibatan ranah kognitif, keterlibatan ranah afektif juga sangat diperlukan melalui penerapan PjBL dalam pendiidkan STEAM. Kwon et al, (2021) (English, 2015), karena semakin banyak sekolah berfokus pada STEM dan mengadopsi strategi pembelajaran STEM (Bicer et al, 2015& Honey et al, 2014…”
Section: Aksioma: Jurnal Program Studi Pendidikan Matematikaunclassified